ANALISIS MOTIVASI PEGAWAI PADA KANTOR DINAS PEKERJAAN UMUM KABUPATEN MAMUJU UTARA - Syahruddin, Syahruddin (Katalogis, 2018)
This study aimed to analyze employee motivation at Mamuju Utara Departmen of Public Works. The method used was qualitative study. The method used in collecting data was interview, direct observation, and documentation.Based on the result, the employee motivation of Mamuju Utara Department of Public Works had been good, for the employees had been motivated to work well in serving people due to their willingness to fulfil their needs for achievement to gain recognition either from their employers or from their fellows. So was the indicator of self-actualization needs, some employees was motivated to work and to increase their knowledge in order to be promoted to higher position behind their service as public servants. Inspite of those indicators, for most of the employees, the social needs was not the motivation to improve their performance. The indicators of physiological needs and security needs had been running well, for cooperation relation had been harmonious in achieving the goals along with improvement of public service quality.